2002
DOI: 10.3171/jns.2002.96.2.0229
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-life assessment in patients who had been surgically treated for cerebellar pilocytic astrocytoma in childhood

Abstract: By traditional standards, these patients appear to fare quite well. Nevertheless, their self-reported life experience is unsatisfying when compared with the control group. The authors conclude that psychosocial factors are critical to complete recovery and the QOL of children who undergo successful operations for benign cerebellar astrocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…The clinical importance of this small difference is therefore questionable. However, our findings are in line with findings from other studies that described impaired HRQoL in similar domains, using other HRQoL measures [9,10,[19][20][21]. The reduced HRQoL on the Motor and Cognitive functioning scales can be explained by the high proportion of neurologic impairments seen in these children.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The clinical importance of this small difference is therefore questionable. However, our findings are in line with findings from other studies that described impaired HRQoL in similar domains, using other HRQoL measures [9,10,[19][20][21]. The reduced HRQoL on the Motor and Cognitive functioning scales can be explained by the high proportion of neurologic impairments seen in these children.…”
Section: Discussionsupporting
confidence: 82%
“…Monitoring of health-related quality of life (HRQoL) is done, for example, in childhood survivors who are treated for a pilocytic astrocytoma [9][10][11], low-grade glioma [12], high-grade glioma [13], craniopharyngioma [14,15], medulloblastoma [16,17], and in heterogeneous groups [18][19][20][21][22][23][24]. In most of these studies, survivors reported a variety of degree of reduction in HRQoL compared with healthy age mates [9,10,[13][14][15][16][18][19][20][21][22][23][24]. This could be explained by the heterogeneity of brain tumors and their treatments.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in line with prior research showing an altogether favorable long-term prognosis of cognitive functioning in CPA patients. 12,15,21,22 Similarly, long-term CPA survivors included in this study were all well integrated into school or professional life. Of those who had finished their education, all were either employed or self-employed.…”
Section: Discussionmentioning
confidence: 99%
“…This result corresponds with a study by Zuzak and colleagues, 22 who found that CPA patients rated their QoL similarly or even higher than healthy controls. Additionally, another study 21 showed that survivors of surgically removed low-grade CPA tend to have a better QoL than other brain tumor patients. As QoL is generally thought to be related to academic achievement and professional status, it may not be surprising to find such good ratings in a patient group that is quite well integrated in educational and professional life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation